Analisis Kesesuaian Standar OLC Quality Scorecard dalam Pendidikan Non-Formal Gamelab ID Academy - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Indonesian Journal Publisher, 2023)
This qualitative research aims to explore and analyze the alignment of OLCQS standards within Gamelab ID Academy, a non-formal education platform designed to assist Vocational School (SMK) students and university students in preparing for the industrial world and the job market (DUDIKA). The OLCQS model analyzes various aspects of Gamelab ID Academy, including instructional design, assessment policies, instructor-student interactions, and the learner experience. The research findings encompass an analysis of the OLC Quality Scorecard, which comprises several components, including Course Overview and Information, Course Technology and Tools, Design and Layout, Content and Activities, Interaction, and Assessment and Feedback. The results of the study indicate that the platform has several strengths, such as online learning flexibility, comprehensive content delivery, and active instructor support. However, there are areas that require improvement, such as the clarity of application tool policies and material accessibility.